A framework for user aware route selection in pedestrian navigation system - Chakraborty, B; Hashimoto, T (2010 2nd International Symposium on Aware Computing, 2010)
With the help of fast and cheap information technology GPS navigators for car navigation are becoming very common. But unlike vehicle users, pedestrians form a more heterogeneous group having different levels of physical abilities with varieties of conditions, personal preferences and needs. The lack of data to support pedestrian navigation also imposes a harder challenge to design generalized navigation system for pedestrians, specially elders and persons with disability. In this work a framework for an user aware pedestrian navigation system is designed in which a fuzzy set theory based algorithm is proposed to analyze the user's requirement from the linguistic expression within limited vocabulary and a genetic algorithm is proposed to generate multiple alternate near optimal routes according to user's need. The optimal route can be decided by user from the options by an interactive mode. A simple simulation experiment has been done to study the feasibility of the development of an user aware, flexible pedestrian navigation system.